Health and social care-associated harm amongst vulnerable children in primary care: mixed methods analysis of national safety reports. Issue 8 (6th March 2020) - Omar, Adhnan; Rees, Philippa; Cooper, Alison; Evans, Huw; Williams, Huw; Hibbert, Peter; Makeham, Meredith; Parry, Gareth; Donaldson, Liam; Edwards, Adrian; Carson-Stevens, Andrew
Abstract : Purpose: Patient safety failures are recognised as a global threat to public health, yet remain a leading cause of death internationally. Vulnerable children are inversely more in need of high-quality primary health and social-care but little is known about the quality of care received. Using national patient safety data, this study aimed to characterise primary care-related safety incidents among vulnerable children. Methods: This was a cross-sectional mixed methods study of a national database of patient safety incident reports occurring in primary care settings. Free-text incident reports were coded to describe incident types, contributory factors, harm severity and incident outcomes. Subsequent thematic analyses of a purposive sample of reports was undertaken to understand factors underpinning problem areas. Results: Of 1183 reports identified, 572 (48%) described harm to vulnerable children. Sociodemographic analysis showed that included children had child protection-related (517, 44%); social (353, 30%); psychological (189, 16%) or physical (124, 11%) vulnerabilities. Priority safety issues included: poor recognition of needs and subsequent provision of adequate care; insufficient provider access to accurate information about vulnerable children, and delayed referrals between providers. Conclusion: This is the first national study using incident report data to explore unsafe care amongst vulnerable children. Several system failures affecting vulnerable children are highlighted, many of which pose internationally recognised challenges to providers aiming to deliver safe care to this at-risk cohort. We encourage healthcare organisations globally to build on our findings and explore the safety and reliability of their healthcare systems, in order to sustainably mitigate harm to vulnerable children.